Legitimasi Pemerintahan Myanmar sebagai Anggota ASEAN Pasca Kudeta Militer Ditinjau dari Prinsip Non Intervensi Hukum Internasional - Ika Fransisca; Arief Satrya Budianto (CV Rewang Rencang, 2025)
This research analyzes the legitimacy of Myanmar's government as an ASEAN member post-2021 military coup through normative juridical research methods. Myanmar's military coup has caused a humanitarian crisis with regional impacts. Research shows that the coup fails to meet defactoism theory parameters and constitutional legitimacy. ASEAN applies the Estrada theory by upholding the non-intervention principle through the Five-Point Consensus, but this approach proves ineffective. ASEAN's non-intervention principle needs reformulation by considering the High Council establishment according to Treaty of Amity and Cooperation, along with strengthened cooperation with the international community in handling coups involving human rights violations